Analysis of Cost, Income, and Feasibility of Areca Nut Seed Breeding Farming Business, Betara District, Tanjung Jabung Barat Regency - Faisal Hamid; Erni Achmad; Zainul Bahri; Etik Umiyati; Nurhayani; Zamzami; Siti Hodijah (Indonesian Journal Economic Review (IJER), 2026)
Indonesia is the ruler of areca nut exports in the world and 40% of Indonesia's total areca nut exports come from Jambi. The research was focus by Jambi’s strategic role in national areca nut production and exports, alongside persistent constraints in the upstream subsystem of agribusiness especially limited capital, production-cost variability, and uneven breeder capacity to consistently meet certification standards. A survey based descriptive quantitative approach was employed. Primary data were collected through structured interviews using questionnaires from three purposively selected certified breeders (from five existing units) who met the criteria of business ownership, a minimum of two years of operation, and active participation in certification. Secondary data were sourced from BPS and relevant provincial agencies. Analysis focused on fixed and variable cost components, total revenue, farm income (TR–TC), and feasibility using the Revenue–Cost (R/C) ratio. Results show that the average total production cost reached Rp 183,266,666/year, comprising seeding costs of Rp 71,889,427 and nursery costs of Rp 111,377,239. Average total revenue was Rp 692,156,067/year, generating an average income of Rp 508,889,401/year (= Rp 42,407,450/month). The mean R/C ratio was 3.5, indicating financial feasibility (R/C > 1). However, substantial income disparities among breeders suggest that scale, managerial capability, and cost control critically determine profitability. Strengthening cost efficiency, optimizing nursery land (including yard-based expansion), and improving compliance support for certification are recommended to enhance sustainability.